Test Design of Fish Attractor to Improve Selectivity of Results on Purse Seine Ship - Eddy Setyo Koenhardono; Sidratul Nugraha (International Journal of Marine Engineering Innovation and Research, 2021)
Indonesia is a country with abundant potential in the field of fisheries. With this abundant amount of fish, of course, many fishing methods have been developed, such as hunting or following the movement of fish and there are methods that only stay at one point, waiting for a group of fish to approach the gathering point. Fish calling devices that only stay at one point can use sound frequencies. By using the frequency of the sound, the fish will gather at the sound source produced by the fish calling tool, Fish Attractor. This study aims to determine the frequency of sound waves in fish species. The method used in this research is to make a tool that can produce sound waves with adjustable frequency, then the instrument testing will be conducted on fish ponds. Based on the design results, the fish calling device is equipped with an Arduino Uno, LCD, Potentiometer, Speaker, Power Amplifier, and Signal Module. In this Fish Attractor tool, the frequency can be set from 0 Hz – 17,000 Hz. With this adjustable sound frequency, it is expected to attract the attention of fish to get closer to the source of the sound frequency of the fish calling device.